Thin film and preparation method thereof, photoelectric device and display device
By using ultraviolet irradiation in OLED and QLED optoelectronic devices to remove ligands on the carrier functional layer, the exciton quenching problem caused by excessive ligand content is solved, and the luminescence efficiency is improved and the service life is extended.
Patent Information
- Application Number
- CN202311873984.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-30
- Publication Date
- 2025-07-01
AI Technical Summary
In existing OLED and QLED optoelectronic devices, the ligand content of the carrier functional layer is too high, resulting in exciton quenching, reducing luminescence efficiency and shortening service life.
By providing a mixed liquid, including metal nanoparticles and inorganic nanoparticles, the latter with ligands on the surface, ultraviolet irradiation is performed to remove ligands on the surface of the inorganic nanoparticles, a thin film with a significantly lower ligand content is prepared, and applied to the carrier functional layer of the optoelectronic device.
It significantly reduces the possibility of non-radiative recombination between ligands and excitons, improves the luminous efficiency of optoelectronic devices, and extends their service life.
Smart Images

Figure CN120239432A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of display technologies, and particularly to a thin film, a preparation method thereof, an optoelectronic device, and a display device. Background Art
[0002] Currently, the widely used optoelectronic devices are organic light-emitting diodes (OLEDs) and quantum dot light-emitting diodes (QLEDs). Due to their excellent display performances such as self-luminescence, simple structure, ultra-thinness, fast response speed, wide viewing angle, low power consumption, and flexible display, OLEDs have become the mainstream technology in the field of display technologies. QLEDs have the advantages of saturated emission light color and adjustable wavelength, and high photoluminescence and electroluminescence quantum yields. In recent years, they have become strong competitors of OLEDs.
[0003] The structures of traditional OLED and QLED devices generally include an anode, a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer, an electron injection layer, and a cathode. Currently, inorganic nanoparticles are often used as the materials for the carrier functional layer. During the synthesis of inorganic nanoparticles, it is easy to introduce excessive ligands, such as hydroxyl groups, on the surface of the inorganic nanoparticles. The excessive ligands will cause continuous quenching of excitons in the light-emitting layer, resulting in a decrease in the lifespan and luminous efficiency of the optoelectronic device.
[0004] Therefore, the content of ligands in the carrier functional layer needs to be further reduced or removed. Summary of the Invention
[0005] In view of this, this application provides a thin film, a preparation method thereof, an optoelectronic device, and a display device.
[0006] The embodiment of this application is implemented as follows. A preparation method of a thin film includes:
[0007] Providing a mixed solution, where the mixed solution includes metal nanoparticles and inorganic nanoparticles, and the surface of the inorganic nanoparticles has ligands;
[0008] Performing ultraviolet irradiation on the mixed solution to obtain a thin film.
[0009] Correspondingly, the embodiment of this application also provides a thin film prepared by the above preparation method.
[0010] Correspondingly, the embodiment of this application also provides an optoelectronic device, including a first electrode, a first carrier functional layer, an optoelectronic functional layer, and a second electrode that are sequentially stacked; the first carrier functional layer includes a thin film prepared by the above preparation method.
[0011] Correspondingly, the embodiment of this application also provides a display device, and the display device includes the above optoelectronic device.
[0012] The preparation method of the thin film provided by this application results in a significant decrease in the ligand content in the thin film, which is beneficial to the exertion of its beneficial properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] In order to more clearly illustrate the technical solutions in the embodiments of this application, the following will briefly introduce the drawings required for the description of the embodiments. Obviously, the drawings in the following description are only some embodiments of this application. For those skilled in the art, without creative efforts, other drawings can also be obtained based on these drawings.
[0014] Figure 1 It is a flowchart of the preparation method of the thin film provided by the embodiment of this application;
[0015] Figure 2 It is a schematic structural diagram of the optoelectronic device provided by the embodiment of this application.
[0016] Reference numerals:
[0017] First electrode 10; first charge carrier functional layer 20; optoelectronic functional layer 30; second electrode 40; second charge carrier functional layer 50. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0018] The following will clearly and completely describe the technical solutions in the embodiments of this application with reference to the drawings in the embodiments of this application. Obviously, the described embodiments are only some embodiments of this application, rather than all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative efforts belong to the scope of protection of this application. In addition, it should be understood that the specific embodiments described here are only used to illustrate and explain this application, and are not used to limit this application.
[0019] In this application, unless otherwise stated, the orientation terms such as "upper" and "lower" usually refer to the upper and lower in the actual use or working state of the device, specifically the drawing direction in the drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "comprising" means "including but not limited to". The use of the terms first, second, third, etc. is only for marking purposes and does not impose a numerical requirement or establish an order.
[0020] In this application, "and / or" describes the association relationship of associated objects and indicates that three relationships can exist. For example, A and / or B can represent: A exists alone, A and B exist simultaneously, and B exists alone. Where A and B can be singular or plural.
[0021] In this application, "at least one" means one or more, and "a plurality" means two or more. "One or several", "at least one (item)" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one (item) among a, b, or c", or "at least one (item) among a, b, and c" can both represent: a, b, c, a - b (i.e., a and b), a - c, b - c, or a - b - c, where a, b, and c can each be single or multiple.
[0022] The various embodiments of this application may exist in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be construed as a rigid limitation on the scope of this application; therefore, it should be considered that the description of the range has specifically disclosed all possible sub - ranges and single values within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub - ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6, and this applies regardless of the range. Additionally, whenever a numerical range is indicated herein, it means including any cited number (fraction or integer) within the indicated range.
[0023] The technical solution of this application is as follows:
[0024] In a first aspect, please refer to Figure 1 , an embodiment of this application provides a method for preparing a thin film, including:
[0025] S11. Provide a mixed solution, the mixed solution includes metal nanoparticles and inorganic nanoparticles, and there are ligands on the surface of the inorganic nanoparticles;
[0026] S12. Perform ultraviolet irradiation on the mixed solution to obtain a thin film.
[0027] In the method for preparing a thin film provided by this application, after the mixed solution is treated with ultraviolet irradiation, the ligands can be converted into free radicals, and the free radicals can undergo redox reactions with the metal nanoparticles, thereby removing the ligands on the surface of the inorganic nanoparticles and oxidizing the metal nanoparticles into metal oxides. When this thin film is applied to the carrier functional layer of optoelectronic devices, the reduction of the ligand content can reduce the quenching caused by non - radiative recombination between the ligands and excitons, improve the luminous efficiency of optoelectronic devices, and extend the service life of optoelectronic devices.
[0028] In the above S11:
[0029] In some embodiments, the ligand includes a hydroxyl group. Under ultraviolet irradiation, the hydroxyl ligand can be converted into hydroxyl radicals, which can undergo redox reactions with metal nanoparticles, thereby removing the hydroxyl ligands on the surface of inorganic nanoparticles and oxidizing the metal nanoparticles into metal oxides.
[0030] In some embodiments, the ligand is connected to the inorganic nanoparticle by a coordination bond, a covalent bond, or a hydrogen bond.
[0031] In some embodiments, the method for preparing the mixed solution includes: providing a first dispersion liquid and metal nanoparticles, where the first dispersion liquid includes inorganic nanoparticles and ligands on the surface of the inorganic nanoparticles; mixing the first dispersion liquid and the metal nanoparticles to obtain a mixed solution.
[0032] Specifically, in some embodiments, the method for preparing the mixed solution includes:
[0033] S111. Provide a first dispersion liquid and a second dispersion liquid. The first dispersion liquid includes inorganic nanoparticles and ligands on the surface of the inorganic nanoparticles, and the second dispersion liquid includes metal nanoparticles;
[0034] S112. Mix the first dispersion liquid and the second dispersion liquid to obtain a mixed solution.
[0035] In some embodiments, the inorganic nanoparticles include P-type inorganic nanoparticles or N-type inorganic nanoparticles.
[0036] Furthermore, the N-type inorganic nanoparticles include one or more of first doped metal oxide particles, first undoped metal oxide particles, IIB-VIA group semiconductor materials, IIIA-VA group semiconductor materials, and IB-IIIA-VIA group semiconductor materials. The materials of the first undoped metal oxide particles include one or more of ZnO, TiO2, SnO2, ZrO2, Ta2O5. The metal oxides in the first doped metal oxide particles include one or more of ZnO, TiO2, SnO2, ZrO2, Ta2O5, Al2O3. The doping elements in the first doped metal oxide particles include one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, Ga. The IIB-VIA group semiconductor materials include one or more of ZnS, ZnSe, CdS. The IIIA-VA group semiconductor materials include one or more of InP, GaP. The IB-IIIA-VIA group semiconductor materials include one or more of CuInS, CuGaS.
[0037] The P-type inorganic nanoparticles include one or more of second doped metal oxide particles, second undoped metal oxide particles, metal sulfides, metal selenides, and metal nitrides. The metal oxides in the second doped metal oxide particles and the metal oxides in the second undoped metal oxide particles independently include one or more of MoO3, WO3, NiO, CrO3, CuO, and V2O5. The doping elements in the second doped metal oxide particles include one or more of Mo, W, Ni, Cr, Cu, and V. The metal sulfides include one or more of CuS, MoS3, and WS3. The metal selenides include one or more of MoSe3 and WSe3. The metal nitrides include p-type gallium nitride.
[0038] In some embodiments, the average particle size of the inorganic nanoparticles is 2 nm to 20 nm, and for example, it can be 5 nm, 8 nm, 10 nm, 12 nm, 15 nm, 18 nm, etc.
[0039] In some embodiments, in the first dispersion liquid, the mass concentration of the inorganic nanoparticles is 10 mg / mL to 50 mg / mL, and for example, it can be 15 mg / mL, 20 mg / mL, 25 mg / mL, 30 mg / mL, 35 mg / mL, 40 mg / mL, 45 mg / mL, etc. Within this mass concentration range, it is beneficial for the inorganic nanoparticles to be fully dissolved and dispersed.
[0040] In some embodiments, the first dispersion liquid further includes a first dispersant.
[0041] Furthermore, the first dispersant includes one or more of chlorobenzene, diethylene glycol monobutyl ether, trimethoxybutanol, triethylene glycol monobutyl ether, diethylene glycol dimethyl ether, methanol, ethanol, propanol, butanol, ethylene glycol, isopropanol, glycerol, dimethyl sulfoxide, acetone, acetophenone, tetrahydrofuran, N,N-dimethylformamide, dimethyl sulfoxide, ethyl acetate, pyrrole, butyric acid, and cresol.
[0042] In some embodiments, the metal nanoparticles include one or more of Zn, Al, Ag, Fe, Mg, and Pt. It can be understood that the metal nanoparticles have high activity and can promote the reaction with free radicals.
[0043] In some embodiments, the average particle size of the metal nanoparticles is 1 nm to 50 nm, and for example, it can be 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, etc.
[0044] In some embodiments, in the second dispersion liquid, the mass concentration of the metal nanoparticles is 1 mg / mL to 10 mg / mL, and can be, for example, 2 mg / mL, 4 mg / mL, 6 mg / mL, 8 mg / mL, etc.
[0045] In some embodiments, the second dispersion liquid further includes a second dispersant.
[0046] Furthermore, the second dispersant includes one or more of chlorobenzene, diethylene glycol monobutyl ether, trimethoxybutanol, triethylene glycol monobutyl ether, diethylene glycol dimethyl ether, methanol, ethanol, propanol, butanol, ethylene glycol, isopropanol, glycerol, dimethyl sulfoxide, acetone, acetophenone, tetrahydrofuran, N,N-dimethylformamide, dimethyl sulfoxide, ethyl acetate, pyrrole, butyric acid, and cresol.
[0047] In some embodiments, in the mixed liquid, the mass ratio of the inorganic nanoparticles to the metal nanoparticles is (4 to 50):1, and can be, for example, 5:1, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1, etc. Within the range of the mass ratio, it is beneficial for the metal nanoparticles to fully react with the ligand free radicals.
[0048] In some embodiments, after the first dispersion liquid and the second dispersion liquid are mixed, stirring is further included.
[0049] Furthermore, the stirring time is 30 min to 120 min, and can be, for example, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, etc. Within the range of the stirring time, it is beneficial for the inorganic nanoparticles and the metal nanoparticles to be fully and uniformly mixed.
[0050] In S12:
[0051] In some embodiments, before ultraviolet irradiation of the mixed liquid, the following steps are further included: providing a substrate and disposing the mixed liquid on the substrate.
[0052] In some embodiments, the power of the ultraviolet irradiation is 100 W to 500 W, and can be, for example, 150 W, 200 W, 250 W, 300 W, 350 W, 400 W, 450 W, etc.; the time of the ultraviolet irradiation is 10 min to 30 min, and can be, for example, 15 min, 20 min, 25 min, etc.
[0053] Thus, under the conditions of the ultraviolet irradiation, it is possible to promote the conversion of the ligand into free radicals and remove them through an oxidation-reduction reaction with the metal nanoparticles.
[0054] In some embodiments, before ultraviolet irradiation of the mixed solution, the following steps are further included: performing a thermal annealing treatment.
[0055] In some embodiments, the temperature of the thermal annealing is 80°C to 100°C, for example, it can be 82°C, 82°C, 82°C, 82°C, 82°C, 82°C, 82°C, 82°C, etc.; the time is 10 min to 30 min, for example, it can be 12 min, 15 min, 18 min, 20 min, 22 min, 25 min, 28 min, etc.
[0056] In some embodiments, after the thermal annealing treatment and before ultraviolet irradiation, the following steps are further included: performing a vacuum treatment.
[0057] Further, the degree of vacuum of the vacuum treatment is 0.01 Pa to 1 Pa, for example, it can be 0.1 Pa, 0.1 Pa, 0.1 Pa, 0.1 Pa, 0.1 Pa, 0.1 Pa, 0.1 Pa, 0.1 Pa, 0.1 Pa, etc.; the time is 10 min to 30 min, for example, it can be 12 min, 15 min, 18 min, 20 min, 22 min, 25 min, 28 min, etc. Under the conditions of the vacuum treatment, it is beneficial to further remove the residual dispersant.
[0058] In some embodiments, the material of the thin film includes inorganic nanoparticles and a third metal oxide.
[0059] The inorganic nanoparticles in the thin film do not contain ligands, or the content of the ligands is less than the content of the ligands in the inorganic nanoparticles in the mixed solution. In other words, the material of the inorganic nanoparticles in the thin film is the same as that of the inorganic nanoparticles in the mixed solution, but the content of its ligands is greatly reduced or even ligand-free. It can be understood that the ligand can be a hydroxyl group.
[0060] The third metal oxide is obtained by the reaction of the metal nanoparticles with free radicals. The third metal oxide can also promote the transport of carriers. The third metal oxide includes one or more of zinc oxide, aluminum oxide, silver oxide, iron(III) oxide, magnesium oxide, and platinum oxide.
[0061] Exemplarily, when the ligand is a hydroxyl group, the chemical formula for the reaction of the hydroxyl radical and the metal nanoparticles is as follows:
[0062] HO· + M → M x O y
[0063] Wherein, M represents the metal nanoparticles described above.
[0064] It should be noted that the H in the hydroxyl radical will react with the OH that has not reacted with the metal nanoparticle M to generate H2O.
[0065] In some embodiments, in the thin film, the mass ratio of the inorganic nanoparticles to the third metal oxide is (4 to 100):1, and can be, for example, 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, etc. In this way, the carrier transport performance of the inorganic nanoparticles can be ensured.
[0066] In some embodiments, the thickness of the thin film is 40 nm to 60 nm, and can be, for example, 42 nm, 45 nm, 48 nm, 50 nm, 52 nm, 55 nm, 58 nm, etc.
[0067] In a second aspect, an embodiment of the present application further provides a thin film prepared by the above preparation method.
[0068] In a third aspect, please refer to Figure 2 , an embodiment of the present application further provides an optoelectronic device, including a first electrode 10, a first carrier functional layer 20, an optoelectronic functional layer 30, and a second electrode 40 that are sequentially stacked; the first carrier functional layer 20 includes a thin film prepared by the above preparation method.
[0069] In the optoelectronic device provided by the present application, the inorganic nanoparticles contain a small amount of ligands or no ligands, which can reduce exciton quenching, improve the luminous efficiency of the optoelectronic device, and extend the service life of the optoelectronic device.
[0070] In some embodiments, the optoelectronic device includes a light-emitting diode.
[0071] In some embodiments, the optoelectronic device further includes a second carrier functional layer 50; the second carrier functional layer 50 is disposed between the optoelectronic functional layer 30 and the second electrode 40. It can be understood that the second carrier functional layer 50 can also be prepared by the above thin film preparation method.
[0072] In some embodiments, the first carrier functional layer 20 is a hole functional layer, and the second carrier functional layer 50 is an electron functional layer. Correspondingly, the first electrode 10 is an anode, and the second electrode 40 is a cathode.
[0073] In other embodiments, the second carrier functional layer 50 is a hole functional layer, and the first carrier functional layer 20 is an electron functional layer. Correspondingly, the second electrode 40 is an anode, and the first electrode 10 is a cathode.
[0074] Further, the hole functional layer includes one or more of a hole injection layer and a hole transport layer.
[0075] The electronic functional layer includes one or more of an electron injection layer and an electron transport layer.
[0076] In some embodiments, the materials of the optoelectronic functional layer 30 include organic light-emitting materials or quantum dots.
[0077] The organic light-emitting materials include one or more of 4,4'-bis(N-carbazolyl)-1,1'-biphenyl: tris[2-(p-tolyl)pyridineiridium(III)], 4,4',4''-tris(carbazol-9-yl)triphenylamine: tris[2-(p-tolyl)pyridineiridium], diarylanthracene derivatives, stilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP fluorescent materials, delayed fluorescence materials, TTA materials, TADF materials, polymers containing B-N covalent bonds, HLCT materials, and Exciplex light-emitting materials.
[0078] In some embodiments, the quantum dots may be selected from, but not limited to, one or more of single-structure quantum dots, core-shell structure quantum dots, and perovskite-type quantum dots.
[0079] The materials of the single-structure quantum dots, the core materials of the core-shell structure quantum dots, and the shell materials of the core-shell structure quantum dots can be respectively selected from, but not limited to, one or several of II-VI group compounds, IV-VI group compounds, III-V group compounds, and I-III-VI group compounds. The shell layer of the core-shell structure quantum dots is one or more layers. The II-VI group compounds can be selected from, but not limited to, one or several of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, and HgZnSTe. The IV-VI group compounds can be selected from, but not limited to, one or several of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe. The III-V group compounds can be selected from, but not limited to, one or several of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, and InAlPSb. The I-III-VI group compounds can be selected from, but not limited to, one or several of CuInS2, CuInSe2, and AgInS2.
[0080] As an example, the core-shell structure quantum dots can be selected from, but not limited to, one or more of CdSe / CdSeS / CdS, InP / ZnSeS / ZnS, CdZnSe / ZnSe / ZnS, CdSeS / ZnSeS / ZnS, CdSe / ZnS, CdSe / ZnSe / ZnS, ZnSe / ZnS, ZnSeTe / ZnS, CdSe / CdZnSeS / ZnS, and InP / ZnSe / ZnS. In the expressions such as CdSe / ZnS above, " / " means that the substance after " / " (as the shell layer) coats the substance before " / " (as the core layer).
[0081] The general structural formula of the perovskite quantum dots is AMX3, where A is selected from Cs + , CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is selected from Pb 2+ , Sn 2+ , Cu 2+ , Ni 2+ , Cd 2+ , Cr 2+ , Mn 2+ , Co 2+ , Fe 2+ , Ge 2+ , Yb 2+ , Eu 2+ and one or more of them, and X is selected from Cl - , Br - , I - and one or more of them.
[0082] In some embodiments, the first electrode 10 and the second electrode 40 each independently include one or more of a metal, a carbon material, and a metal oxide; the metal includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb, and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene, and carbon fibers; the metal oxide includes a metal oxide electrode or a composite electrode with a metal disposed between doped or undoped transparent metal oxides. The material of the metal oxide electrode includes one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO, MoO3, and AMO. The composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2, and TiO2 / Al / TiO2. Herein, " / " represents a stacked structure. For example, AZO / Ag / AZO represents a composite electrode including a sequentially stacked AZO layer, an Ag layer, and an AZO layer.
[0083] It can be understood that when the electronic functional layer is prepared by the above-mentioned thin film preparation method, the material of the electronic functional layer includes N-type inorganic nanoparticles and a third metal oxide; when the electronic functional layer is not prepared by the above-mentioned thin film preparation method, the material of the electronic functional layer includes one or more of first doped metal oxide particles, first undoped metal oxide particles, IIB-VIA group semiconductor materials, IIIA-VA group semiconductor materials, and IB-IIIA-VIA group semiconductor materials. The material of the first undoped metal oxide particles includes one or more of ZnO, TiO2, SnO2, ZrO2, and Ta2O5. The metal oxides in the first doped metal oxide particles include one or more of ZnO, TiO2, SnO2, ZrO2, Ta2O5, and Al2O3. The doping elements in the first doped metal oxide particles include one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, and Ga. The IIB-VIA group semiconductor materials include one or more of ZnS, ZnSe, and CdS. The IIIA-VA group semiconductor materials include one or more of InP and GaP. The IB-IIIA-VIA group semiconductor materials include one or more of CuInS and CuGaS.
[0084] It can be understood that when the hole functional layer is prepared by the above-mentioned method for preparing the thin film, the material of the hole functional layer includes P-type inorganic nanoparticles and a third metal oxide;When the hole functional layer is not prepared by the above-mentioned thin film preparation method, the materials of the hole functional layer include 4,4'-N,N'-dicarbazolyl-biphenyl, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4”-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, 4,4',4'-tris(N-carbazolyl)-triphenylamine, 4,4',4'-tris(carbazol-9-yl)triphenylamine, trichloroisocyanuric acid, terbium-doped phosphate-based green light-emitting material, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(4-butylphenyl-diphenylamine), poly[bis(4-phenyl)(4-butylphenyl)amine], polyaniline, polypyrrole, poly(p-phenylene vinylene), poly(phenylene vinylene), poly[2-methoxy-5-(2-ethylhexoxy)-1,4-phenylene vinylene], poly[2-methoxy-5-(3',7'-dimethyloctoxy)-1,4-phenylene vinylene], copper phthalocyanine, aromatic tertiary amine, polynuclear aromatic tertiary amine, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compound, N,N,N',N'-tetraarylbenzidine, PEDOT, PEDOT:PSS and its derivatives, PEDOT:PSS derivatives doped with s-MoO3, poly(N-vinylcarbazole) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, N,N'-bis(naphthalen-1-yl)-N,N'-diphenylbenzidine, spiro-NPB, nanocrystalline diamond, microcrystalline cellulose and tetracyanoquinodimethane, doped graphene, undoped graphene, second doped metal oxide particles, second undoped metal oxide particles, metal sulfides, metal selenides and metal nitrides, wherein the metal oxides in the second doped metal oxide particles and the metal oxides in the second undoped metal oxide particles independently include one or more of MoO3, WO3, NiO, CrO3, CuO, V2O5, the doping elements in the second doped metal oxide particles include one or more of Mo, W, Ni, Cr, Cu, V, the metal sulfides include one or more of CuS, MoS3, WS3, the metal selenides include one or more of MoSe3, WSe3, and the metal nitrides include p-type gallium nitride.;
[0085] In a fourth aspect, an embodiment of the present application further provides a display device, and the display device includes the above optoelectronic device.
[0086] The display device may be any electronic product with a display function, and the electronic product includes but is not limited to a smart phone, a tablet computer, a laptop computer, a digital camera, a digital video camera, a smart wearable device, a smart weighing electronic scale, a vehicle-mounted display, a television, or an e-book reader. Among them, the smart wearable device may be, for example, a smart bracelet, a smart watch, a virtual reality (VR) helmet, etc.
[0087] The following specifically describes the present application through specific embodiments. The following embodiments are only partial embodiments of the present application and do not limit the present application.
[0088] Embodiment 1
[0089] This embodiment provides a thin film, and the preparation method includes:
[0090] Mix 0.1 mL of a 10 mg / ml dispersion of Ag into 0.5 mL of a 40 mg / mL ethanol dispersion of ZnO. The ZnO contains hydroxyl groups, and stir for 30 min to obtain a mixed solution;
[0091] Provide a substrate, set the mixed solution on the substrate, anneal at 80 °C for 20 min, perform vacuum treatment for 10 min, and then excite with ultraviolet light of 400 W for 20 min to obtain a thin film.
[0092] Embodiments 2 to 3
[0093] Embodiments 2 to 3 are basically the same as Embodiment 1, except that
[0094] In Embodiment 2, the dispersion of Ag is 0.1 mL, and the ethanol dispersion of ZnO is 0.125 mL;
[0095] In Embodiment 3, the dispersion of Ag is 0.1 mL, and the ethanol dispersion of ZnO is 1 mL.
[0096] Embodiments 4 to 7
[0097] Embodiments 4 to 7 are basically the same as Embodiment 1, except that
[0098] In Embodiments 4 to 6, the power of ultraviolet excitation is 500 W and 100 W respectively;
[0099] In Embodiments 6 to 7, the time of ultraviolet excitation is 30 min and 10 min respectively.
[0100] Embodiments 8 to 11
[0101] Examples 8 to 11 are basically the same as Example 1, except that
[0102] in Examples 8 to 9, metal Ag is replaced with Mg and Pt respectively;
[0103] in Examples 10 to 11, ZnO is replaced with TiO2 and NiO respectively.
[0104] Comparative Example 1
[0105] This comparative example is basically the same as Example 1, except that in this comparative example, metal Ag is not added and ultraviolet excitation treatment is not carried out.
[0106] Comparative Example 2
[0107] This comparative example is basically the same as Example 1, except that in this comparative example, ultraviolet excitation treatment is not carried out.
[0108] Comparative Example 3
[0109] This comparative example is basically the same as Example 1, except that in this comparative example, metal Ag is not added.
[0110] The O element in the thin films of Examples 1 to 11 and Comparative Examples 1 to 3 was tested by XPS, and the content ratio of OH in the total O element was obtained. The test results are shown in Table 1.
[0111] Table 1
[0112]
[0113]
[0114] As can be seen from Table 1:
[0115] From Examples 1 to 3 and Comparative Examples 1 to 3, it can be obtained that for the thin films prepared by the preparation method of the present application, the hydroxyl content decreases significantly; in Comparative Examples 1 to 3, without adding metal or without ultraviolet treatment, the hydroxyl content has little difference; while in Examples 1 to 3, a large amount of hydroxyl is removed by the redox reaction of the hydroxyl radicals obtained by the metal and ultraviolet treatment;
[0116] From Examples 1, 4 to 7 and Comparative Example 1, it can be obtained that within the range provided by the present application, the power and time of ultraviolet irradiation treatment have a certain influence on the hydroxyl content. The greater the power of ultraviolet irradiation treatment and the longer the time, the less the hydroxyl content;
[0117] From Example 1, Examples 8-11 and Comparative Example 1, it can be seen that by replacing the metal and semiconductor materials, there are slight differences in the hydroxyl content in the thin film, mainly due to the reactivity of the metal and the hydroxyl content introduced during the synthesis process of the semiconductor material itself. Compared with Comparative Example 1, the hydroxyl content has significantly decreased, which is beneficial to the performance of the thin film.
[0118] Device Example 1
[0119] This example provides an optoelectronic device, and the preparation method is as follows:
[0120] Clean the ITO conductive glass with a cleaner to initially remove the stains on the surface, and then ultrasonically clean it in deionized water, acetone, absolute ethanol, and deionized water for 20 minutes respectively to remove the impurities on the surface. Finally, dry it with high-purity nitrogen to obtain the ITO anode;
[0121] Place the ITO substrate on a spin coater and spin coat it with the prepared TFB solution at a spin speed of 3000 rpm for 30 s; after spin coating, perform a thermal annealing treatment at 150 °C for 30 min to form a 30-nm hole transport layer;
[0122] Place the substrate with the spin-coated hole transport layer on a spin coater and spin coat it with the prepared CdZnSe / ZnSe / ZnS quantum dot solution at a spin speed of 3000 rpm for 30 s; after spin coating, perform a thermal annealing treatment at 80 °C for 30 min to form a light-emitting layer with a thickness of 40 nm;
[0123] Refer to Example 1 to prepare the electron transport layer;
[0124] Place the substrate deposited with each functional layer in an evaporation chamber and thermally evaporate a 60-nm layer of metallic silver as the cathode through a mask plate;
[0125] Encapsulate under the conditions that both the oxygen content and the water content are lower than 0.1 ppm to obtain the optoelectronic device.
[0126] Device Examples 2-10
[0127] Device Examples 2-10 are basically the same as Device Example 1, except that in Device Examples 2-10, the electron transport layers are prepared by referring to Examples 2-10 respectively.
[0128] Device Examples 11-12
[0129] Device Examples 11-12 are basically the same as Device Example 1, except that
[0130] In Device Example 11, the electron transport layer is prepared by referring to Comparative Example 1, and the hole transport layer is prepared by using Example 11;
[0131] In Device Example 12, the hole transport layer was further prepared with reference to Example 11.
[0132] Device Comparative Examples 1-4
[0133] Device Comparative Examples 1-4 were basically the same as Device Example 1, except that
[0134] in Device Comparative Examples 1-3, the hole transport layer was prepared with reference to Comparative Examples 1-3;
[0135] in Device Comparative Example 4, the material of the hole transport layer in Device Comparative Example 1 was replaced with conventional NiO.
[0136] The external quantum efficiency EQE and the lifetime T95@1000nit of Device Examples 1-12 and Device Comparative Examples 1-4 were respectively tested, and the results are as described in Table 2.
[0137] Among them, the test method for the external quantum efficiency EQE is: the ratio of the number of electron-hole pairs injected into the quantum dots to the number of emitted photons, with the unit of %, which is an important parameter to measure the quality of the electroluminescent device and can be obtained by measuring with an EQE optical test instrument. The specific calculation formula is as follows:
[0138]
[0139] Among them, η e is the optical output coupling efficiency, η r is the ratio of the number of recombined carriers to the number of injected carriers, χ is the ratio of the number of excitons generating photons to the total number of excitons, K R is the radiation process rate, K NR is the non-radiation process rate.
[0140] Test conditions: carried out at room temperature, with the air humidity of 30-60%.
[0141] The test method for the lifetime T95@1000nit is: the time required for the device to reduce the brightness to a certain proportion of the maximum brightness under a constant current or voltage drive. The time when the brightness drops to 95% of the maximum brightness is defined as T95, and this lifetime is the measured lifetime. To shorten the test cycle, the device lifetime test is usually carried out by accelerating the device aging at a high brightness and fitting the lifetime at the high brightness through an extended exponential decay brightness decay fitting formula, such as: the lifetime at 1000nit is denoted as T95@1000nit. The specific calculation formula is as follows:
[0142]
[0143] Among them, T95 L is the lifetime at a low brightness, T95 HIs the measured life at high brightness, L H Is the device accelerated to the highest brightness, L L Is 1000 nit, A is the acceleration factor. In this experiment, the value of A is obtained as 1.7 by measuring the lifetimes of several groups of QLED devices at the rated brightness.
[0144] Table 2
[0145]
[0146] As can be seen from Table 2:
[0147] From Device Examples 1-3 and Device Comparative Examples 1-3, it can be obtained that when the thin film obtained by the preparation method of the present application is applied to the electron transport layer in optoelectronic devices, the external quantum efficiency of the optoelectronic devices is significantly improved, and the service life is also significantly extended; in Device Comparative Examples 1-3, only adding metal or only performing ultraviolet treatment on the electron transport layer, the performance of the optoelectronic devices is still worse than that of Conventional Device Comparative Example 1; while in Device Examples 1-3, after removing a large amount of hydroxyl groups, the non-radiative recombination of hydroxyl groups and excitons is reduced, thereby improving the performance of the optoelectronic devices;
[0148] From Device Examples 1, 4-7 and Device Comparative Example 1, it can be obtained that within the scope provided by the present application, the difference in the power and time of ultraviolet irradiation treatment has no significant impact on the external quantum efficiency and service life of optoelectronic devices, and the performance of optoelectronic devices is improved compared with Example 1;
[0149] From Device Examples 1, 8-10 and Device Comparative Example 1, it can be obtained that when replacing the metal and semiconductor materials, the reactivity of the metal will affect the recombination with hydroxyl radicals to a certain extent, and there are certain differences in the electron mobility of the semiconductor materials themselves. Generally speaking, compared with Device Comparative Example 1, it promotes the improvement of the external quantum efficiency and service life;
[0150] From Device Examples 11-12 and Device Comparative Example 4, it can be obtained that using the method provided by the present application to prepare the hole transport layer can also significantly improve the external quantum efficiency and service life of optoelectronic devices. Especially compared with Device Comparative Example 4, the external quantum efficiency and service life of Device Example 11 are significantly improved.
[0151] The thin film, its preparation method, optoelectronic devices, and display devices provided by the embodiments of the present application have been introduced in detail above. Specific examples are used in this article to elaborate on the principles and implementation manners of the present application. The descriptions of the above embodiments are only used to help understand the method and its core idea of the present application; at the same time, for those skilled in the art, according to the idea of the present application, there will be changes in the specific implementation manners and application scopes. In summary, the content of this specification should not be construed as a limitation to the present application.
Claims
1. A method for preparing a thin film, characterized in that, Comprising: Providing a mixed solution, which includes metal nanoparticles and inorganic nanoparticles, and ligands are present on the surface of the inorganic nanoparticles; Performing ultraviolet irradiation on the mixed solution to obtain a thin film.
2. The preparation method according to claim 1, wherein The ligand includes a hydroxyl group; and / or The ligand is connected to the inorganic nanoparticles through a coordination bond, a covalent bond or a hydrogen bond; and / or In the mixed solution, the mass ratio of the inorganic nanoparticles to the metal nanoparticles is (4 to 50):1; and / or The inorganic nanoparticles include P-type inorganic nanoparticles or N-type inorganic nanoparticles; and / or The average particle size of the inorganic nanoparticles is 2 nm to 20 nm; and / or The metal nanoparticles include one or more of Zn, Al, Ag, Fe, Mg, Pt; and / or The average particle size of the metal nanoparticles is 1 nm to 50 nm.
3. The preparation method according to claim 2, wherein The N-type inorganic nanoparticles include one or more of first doped metal oxide particles, first undoped metal oxide particles, IIB-VIA group semiconductor materials, IIIA-VA group semiconductor materials, and IB-IIIA-VIA group semiconductor materials. The materials of the first undoped metal oxide particles include one or more of ZnO, TiO2, SnO2, ZrO2, Ta2O5. The metal oxides in the first doped metal oxide particles include one or more of ZnO, TiO2, SnO2, ZrO2, Ta2O5, Al2O3. The doping elements in the first doped metal oxide particles include one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, Ga. The IIB-VIA group semiconductor materials include one or more of ZnS, ZnSe, CdS. The IIIA-VA group semiconductor materials include one or more of InP, GaP. The IB-IIIA-VIA group semiconductor materials include one or more of CuInS, CuGaS; and / or The P-type inorganic nanoparticles include one or more of second doped metal oxide particles, second undoped metal oxide particles, metal sulfides, metal selenides, and metal nitrides. The metal oxides in the second doped metal oxide particles and the metal oxides in the second undoped metal oxide particles each independently include one or more of MoO3, WO3, NiO, CrO3, CuO, V2O5. The doping elements in the second doped metal oxide particles include one or more of Mo, W, Ni, Cr, Cu, V. The metal sulfides include one or more of CuS, MoS3, WS3. The metal selenides include one or more of MoSe3, WSe3. The metal nitrides include P-type gallium nitride.
4. The preparation method according to claim 1, characterized in that, The preparation method of the mixed solution includes: A first dispersion liquid and metal nanoparticles are provided. The first dispersion liquid includes inorganic nanoparticles and ligands on the surface of the inorganic nanoparticles; The first dispersion liquid and the metal nanoparticles are mixed to obtain a mixed liquid.
5. The preparation method according to claim 4, wherein, In the first dispersion liquid, the mass concentration of the inorganic nanoparticles is 10 mg / mL to 50 mg / mL; and / or The first dispersion liquid further includes a first dispersant; the first dispersant includes one or more of chlorobenzene, diethylene glycol monobutyl ether, trimethoxybutanol, triethylene glycol monobutyl ether, diethylene glycol dimethyl ether, methanol, ethanol, propanol, butanol, ethylene glycol, isopropanol, glycerol, dimethyl sulfoxide, acetone, acetophenone, tetrahydrofuran, N,N-dimethylformamide, dimethyl sulfoxide, ethyl acetate, pyrrole, butyric acid, cresol; and / or After the first dispersion liquid and the metal nanoparticles are mixed, stirring is further included; the stirring time is 30 min to 120 min.
6. The preparation method according to claim 1, wherein, The power of the ultraviolet irradiation is 100 W to 500 W; and / or The time of the ultraviolet irradiation is 10 min to 30 min.
7. The preparation method according to claim 1, wherein, Before the mixed liquid is subjected to ultraviolet irradiation, the following is further included: performing a thermal annealing treatment; the temperature of the thermal annealing is 80 °C to 100 °C; the time is 10 min to 30 min; After the thermal annealing treatment and before the ultraviolet irradiation, the following is further included: performing a vacuum treatment; the degree of vacuum of the vacuum treatment is 0.01 Pa to 1 Pa; the time is 10 min to 30 min.
8. The preparation method according to claim 1, characterized in that, The material of the thin film includes inorganic nanoparticles and a third metal oxide; In the thin film, the inorganic nanoparticles do not contain ligands, or the content of the ligands is less than the content of the ligands in the inorganic nanoparticles in the mixed liquid; and / or The third metal oxide includes one or more of zinc oxide, aluminum oxide, silver oxide, iron(III) oxide, magnesium oxide, platinum oxide; and / or In the thin film, the mass ratio of the inorganic nanoparticles to the third metal oxide is (4 to 100):1; and / or The thickness of the thin film is 40 nm to 60 nm.
9. A film, characterized in that, Prepared by the preparation method according to any one of claims 1 to 8.
10. An optoelectronic device, characterized in that, It includes a first electrode, a first carrier functional layer, a photoelectric functional layer, and a second electrode which are sequentially stacked; the first carrier functional layer includes a thin film, and the thin film is prepared by the preparation method according to any one of claims 1 to 8.
11. The optoelectronic device according to claim 10, wherein, The optoelectronic device further includes a second carrier functional layer; the second carrier functional layer is disposed between the photoelectric functional layer and the second electrode; The first carrier functional layer is a hole functional layer, and the second carrier functional layer is an electron functional layer; or, the second carrier functional layer is a hole functional layer, and the first carrier functional layer is an electron functional layer.
12. The optoelectronic device according to claim 11, wherein, The first electrode and the second electrode each independently include one or more of a metal, a carbon material, and a metal oxide; the metal includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb, and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene, and carbon fiber; the metal oxide includes a metal oxide electrode or a composite electrode with a metal disposed between doped or undoped transparent metal oxides, the material of the metal oxide electrode includes one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO, MoO3, and AMO, and the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2, and TiO2 / Al / TiO2; and / or The material of the optoelectronic functional layer includes one of organic light-emitting materials or quantum dots; the organic light-emitting materials include one or more of 4,4'-bis(N-carbazolyl)-1,1'-biphenyl: tris[2-(p-tolyl)pyridineiridium(III)], 4,4',4”-tris(carbazol-9-yl)triphenylamine: tris[2-(p-tolyl)pyridineiridium], diarylanthracene derivatives, stilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP fluorescent materials, delayed fluorescence materials, TTA materials, TADF materials, polymers containing B-N covalent bonds, HLCT materials, Exciplex luminescent materials; the quantum dots are selected from one or more of single-structure quantum dots, core-shell structure quantum dots and perovskite-type quantum dots; the materials of the single-structure quantum dots, the core materials of the core-shell structure quantum dots and the shell materials of the core-shell structure quantum dots are respectively selected from one or more of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds; the shell layer of the core-shell structure quantum dots is one or more layers, and the II-VI group compounds are selected from one or more of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe; the IV-VI group compounds are selected from one or more of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe;The III-V compound is selected from one or more of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb; the I-III-VI compound is selected from one or more of CuInS2, CuInSe2 and AgInS2; the core-shell structure quantum dot is selected from one or more of CdSe / CdSeS / CdS, InP / ZnSeS / ZnS, CdZnSe / ZnSe / ZnS, CdSeS / ZnSeS / ZnS, CdSe / ZnS, CdSe / ZnSe / ZnS, ZnSe / ZnS, ZnSeTe / ZnS, CdSe / CdZnSeS / ZnS and InP / ZnSe / ZnS; the structural general formula of the perovskite quantum dot is AMX3, where A is selected from Cs; + 、CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is selected from Pb 2+ 、Sn 2+ 、Cu 2+ 、Ni 2+ 、Cd 2+ 、Cr 2+ 、Mn 2+ 、Co 2+ 、Fe 2+ 、Ge 2+ 、Yb 2+ 、Eu 2+ one or more of, and X is selected from Cl - 、Br - 、I - one or more of; and / or When the electronic functional layer includes the thin film, the material of the electronic functional layer includes N-type inorganic nanoparticles and a third metal oxide; when the electronic functional layer does not include the thin film, the material of the electronic functional layer includes one or more of first doped metal oxide particles, first undoped metal oxide particles, IIB-VIA group semiconductor materials, IIIA-VA group semiconductor materials, and IB-IIIA-VIA group semiconductor materials. The material of the first undoped metal oxide particles includes one or more of ZnO, TiO2, SnO2, ZrO2, and Ta2O5. The metal oxides in the first doped metal oxide particles include one or more of ZnO, TiO2, SnO2, ZrO2, Ta2O5, and Al2O3. The doping elements in the first doped metal oxide particles include one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, and Ga. The IIB-VIA group semiconductor materials include one or more of ZnS, ZnSe, and CdS. The IIIA-VA group semiconductor materials include one or more of InP and GaP. The IB-IIIA-VIA group semiconductor materials include one or more of CuInS and CuGaS; and / or When the hole functional layer includes the thin film, the material of the hole functional layer includes P-type inorganic nanoparticles and a third metal oxide;When the hole functional layer does not include the thin film, the materials of the hole functional layer include 4,4'-N,N'-dicarbazolyl-biphenyl, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4”-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, 4,4',4'-tris(N-carbazolyl)-triphenylamine, 4,4',4'-tris(carbazol-9-yl)triphenylamine, trichloroisocyanuric acid, terbium-doped phosphate-based green luminescent material, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(4-butylphenyl-diphenylamine), poly[bis(4-phenyl)(4-butylphenyl)amine], polyaniline, polypyrrole, poly(p-phenylene vinylene), poly(phenylene vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene], poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene], copper phthalocyanine, aromatic tertiary amine, polynuclear aromatic tertiary amine, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compound, N,N,N',N'-tetraarylbenzidine, PEDOT, PEDOT:PSS and its derivatives, PEDOT:PSS derivatives doped with s-MoO3, poly(N-vinylcarbazole) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, N,N'-bis(naphthalen-1-yl)-N,N'-diphenylbenzidine, spiro-NPB, nanocrystalline diamond, microcrystalline cellulose and tetracyanoquinodimethane, doped graphene, undoped graphene, second doped metal oxide particles, second undoped metal oxide particles, metal sulfides, metal selenides and metal nitrides, one or more of which, the metal oxides in the second doped metal oxide particles and the metal oxides in the second undoped metal oxide particles independently include one or more of MoO3, WO3, NiO, CrO3, CuO, V2O5, the doping elements in the second doped metal oxide particles include one or more of Mo, W, Ni, Cr, Cu, V, the metal sulfides include one or more of CuS, MoS3, WS3, the metal selenides include one or more of MoSe3, WSe3, and the metal nitrides include p-type gallium nitride.; 13. A display device, characterized in that, A photoelectric device according to any one of claims 10 to 12 is included.